1998
DOI: 10.1111/j.1572-0241.1998.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of a Teaching Model to Determine Competency in Performing Flexible Sigmoidoscopies

Abstract: The teaching model method offers objective criteria to evaluate skill in performing flexible sigmoidoscopies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…125 In the reviewed literature and in other publications, most definitions have embedded within them a minimum standard needed to be safe and/or the ability to perform the operation independently without help. 31,35,45,48,51,53,55,56,[58][59][60][61][62]64,87,103,[105][106][107]109,110,[113][114][115] Surgical competence has been described as a collection of skill, knowledge, and judgment required to complete new or familiar tasks incorporating both technical and nontechnical (ie, clinical problem solving) components. [119][120][121] Furthermore, operative competence builds on this definition but also includes a surgeon's experience and opportunities to form a broader, more universal domain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…125 In the reviewed literature and in other publications, most definitions have embedded within them a minimum standard needed to be safe and/or the ability to perform the operation independently without help. 31,35,45,48,51,53,55,56,[58][59][60][61][62]64,87,103,[105][106][107]109,110,[113][114][115] Surgical competence has been described as a collection of skill, knowledge, and judgment required to complete new or familiar tasks incorporating both technical and nontechnical (ie, clinical problem solving) components. [119][120][121] Furthermore, operative competence builds on this definition but also includes a surgeon's experience and opportunities to form a broader, more universal domain.…”
Section: Discussionmentioning
confidence: 99%
“…31,35,45,48,51,53,55,56,[58][59][60][61][62]64,87,103,[105][106][107]109,110,[113][114][115] Differentiating competence from proficiency in the reviewed literature demonstrated that a proficient performer is one who approaches expertise and is thus at an advanced stage compared with a competent performer. 56,62,66,67,69,73,75,76,78-80,82-84,87-89,92-94, 96,97,100,113,116 …”
Section: Definition Of Technical Competencementioning
confidence: 93%
See 2 more Smart Citations
“…37 A formalised training programme may allow determination of competency in the performance of FS. 38 Understanding the indications and contraindications for FS are part of the cognitive process. Initial hands-on training begins with time spent becoming familiar with the technical aspects of handling the sigmoidoscope by practising on a plastic model.…”
Section: Training In Fsmentioning
confidence: 99%